Mentoring of Pregnant Women at High Risk Program (Gerdaristi) to Reduce Maternal and Infant Mortality in Nganjuk, East Java - Ratnaningsih, Titin; Joebagio, Hermanu; Murti, Bhisma (Journal of Maternal and Child Health, 2016)
Background: Maternal and infant mortality has the third rank in East Java. The effort to reduce the number of maternal and infant mortality is through Mentoring Program Pregnancy and High Risk Infants Mortality or Gerakan Pendampingan Ibu Hamil Beresiko Tinggi (Gerdaristi). This study aimed to investigate the success rate of implementation of Gerdaristi program in reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Nganjuk.Subjects and Method: This was a case study with qualitative method. This was conducted in Nganjuk, East Java. ÃÂ A sample of 10 pregnant women, 4 cadres, 2 coordinator midwives, 2 community leaders, 1 of the IBI informant, 2 key informant from department of health were selected by using purposive sampling. The data collection used interview, Focus Group Discussion (FGD), observation and documentation. The data were analyzed by chain of evidence, triangulation, member check, checks the extension of participation and colleagues.Results: Implementation Gerdaristi program every month hosted in the health center.ÃÂ  Cadres assisted health centers and conducted home visits every week. Gerdaristi program success is as high as the number of maternal and infant mortality from year to year decline. Nevertheless they found several things including not maximal assistance from the volunteer and mothers level of knowledge about high risk pregnancies are still lacking, and still have a maternal and infant mortality in some districts. This is due to several factors that inhibit awareness among pregnant women to give birth at the hospital as well as their lower mortality factor that cannot be predicted from the beginning.Conclusion: Gerdaristi program has been implemented in accordance with the initial plan involving several related sectors, although there is a few things that implementation is not optimal, but rated this program has been quite successful.Keywords: gerdaristi program, maternal mortality rate, infant mortality rateCorrespondence:ÃÂ Titin Ratnaningsih. Masters Program in Public Health, Sebelas Maret University, Surakarta.Journal of Maternal and Child Health (2016), 1(4): 268-276https://doi.org/10.26911/thejmch.2016.01.04.08